Clinical skills Lab: A Need in Nepalese Medical School - Dhakal, Ajaya Kumar; Dhakal, Sanjaya (Journal of Patan Academy of Health Sciences, 2015)
Medicine of present world demands high level of competency in both clinical examination and performing a procedure in patients. The traditional methods of bedside skill learning and teaching should be supplemented by instruction in clinical skills lab of basic important clinical skills. Every medical school should work towards establishment and incorporation of clinical skills lab in basics science subjects and clinical posting along with other subjects to make it Practice oriented and Student centred learning. Journal of Patan Academy of Health Sciences. 2014 Jun;1(1):49-51